The Conceptualization of Volunteering Among Nonvolunteers: Using the Net-Cost Approach to Expand Definitions and Dimensions of Volunteering. (April 2019) - Haski-Leventhal, Debbie; Oppenheimer, Melanie; Holmes, Kirsten; Lockstone-Binney, Leonie; Alony, Irit; Ong, Faith
Based on the four dimensions of volunteering (time, object, nature, and environment) and net-cost analysis theory, this article examines the conceptualization of volunteering among nonvolunteers and what could attract them to volunteer (attractors). Using flashcard images of volunteering activities among a nationally representative sample in Australia, we reveal nonvolunteers perceived the existing four dimensions of volunteering and, in addition, two new dimensions of volunteering emerged: ability (required skill level) and social (who one volunteers with). Of these dimensions, object, nature, and abilities were found to be the most attractive dimensions of volunteering to nonvolunteers. The study further partially supports the use of net-cost theory as a framework for linking nonvolunteer's perceptions of volunteering to their likelihood of volunteering, with the findings suggesting that low net-cost activities are more attractive to nonvolunteers.